Les enjeux de la citation dans deux préfaces métatraductives d’André Gide - Joanna Jakubowska (Romanica Wratislaviensia)
André Gide was very attached to the question of translation, both as an attentive reader of foreign authors and as a translator himself. He shared his translational observations in numerous writings, two of which we have chosen as the subject of our analysis. These are the foreword to Pushkin’s La Dame de Pique retranslation (1923) and the foreword to Shakespeare’s Théâtre published in French by Gallimard in 1938. In a comparative approach drawing on the methods of enunciative analysis, we study the modalities and stakes of the quotation in the two texts in order to show the evolution in the way Gide constructed his enunciative position and point of view.